2002
DOI: 10.1161/01.cir.0000015126.83143.b4
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Antagonism and Interleukin-6 Inhibition Attenuate the Proatherogenic Effects of C-Reactive Protein

Abstract: Background-C-reactive protein (CRP) has been suggested to actively participate in the development of atherosclerosis.In the present study, we examined the role of the potent endothelium-derived vasoactive factor endothelin-1 (ET-1) and the inflammatory cytokine interleukin-6 (IL-6) as mediators of CRP-induced proatherogenic processes. Methods and Results-Saphenous vein endothelial cells (HSVECs) were incubated with human recombinant CRP (25 g/mL, 24 hours) and the expression of vascular cell adhesion molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
399
3
32

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(444 citation statements)
references
References 44 publications
10
399
3
32
Order By: Relevance
“…ET-1 synthesis and release were increased on exposure to inflammatory cytokines such as TNFa and C-reactive protein in mesangial and vascular endothelial cells. 25,26 Indeed, the blockade of inflammation by a TNFa inhibitor suppressed renal injury in DOCA-salt rats. 27 In this study, ET-1 expression was increased in association with the upregulation of inflammatory chemokines (TNFa, IL-1b and IFNg) and adhesion molecules (MCP-1 and ICAM-1) in DOCA-salt hypertension, and these effects were counteracted by RGT.…”
Section: Effects Of Rosiglitazone On Doca-salt Hypertension Eh Bae Et Almentioning
confidence: 99%
“…ET-1 synthesis and release were increased on exposure to inflammatory cytokines such as TNFa and C-reactive protein in mesangial and vascular endothelial cells. 25,26 Indeed, the blockade of inflammation by a TNFa inhibitor suppressed renal injury in DOCA-salt rats. 27 In this study, ET-1 expression was increased in association with the upregulation of inflammatory chemokines (TNFa, IL-1b and IFNg) and adhesion molecules (MCP-1 and ICAM-1) in DOCA-salt hypertension, and these effects were counteracted by RGT.…”
Section: Effects Of Rosiglitazone On Doca-salt Hypertension Eh Bae Et Almentioning
confidence: 99%
“…Although its role as a biomarker or a mediator of atherosclerosis is still debated, CRP actively contributes to all stages of atherogenesis, including endothelial dysfunction, atherosclerotic-plaque formation, maturation, destabilization and eventual rupture [1,[7][8][9]. A high concentration of hsCRP has been shown to be a strong independent risk factor for cardiovascular events [1,2,[10][11][12], thus, adding prognostic information to traditional risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…These studies, using Abs to CRP and ApoB, or labeled LDL, revealed that CRP did not prevent uptake of modified LDL by macrophages. When measured indirectly by CD32 internalization, CRP was found to increase LDL uptake; however, the involvement of CD32 was questioned (29,32). These studies did not reveal the function of CRP in preventing formation of foam cells, probably because Nile red staining was not used to visualize cholesteryl esters.…”
Section: Discussionmentioning
confidence: 99%